Thin-shell structures; theory, experiment and design : [proceedings] / Edited by Y. C. Fung and E. E. Sechler. - Fung Y. C.1919
"Sponsored by the California Institute of Technology, the United States Air Force, Office of Scientific Research, and the United States Navy, Office of Naval Research."